To go, or not to go? Modelling the effects of employment decentralisation on telecommuting preferences - Tahir, Muhammad Sofian Mohamed (2022)
Employment decentralisation and telecommuting are both gaining popularity as urban and transport demand management strategies. However, as employment shifts to new economic centres that are developed nearer homes, the disamenities related to commuting to the Central Business District (CBD) become less relevant. This potentially induces existing telecommuters to instead travel to their workplaces, influencing the extent to which telecommuting minimises commuting. This study aims to establish a framework to model the effects of employment decentralisation on existing telecommuters by modelling their commute preferences based on two inductive effects on travel: reduction of commute times due to nearer workplaces and reduced crowdedness due to the dispersion of unidirectional CBD-bound travels. A structural equation model was developed from a stated preference survey depicting various workplace locations, crowdedness levels and commute times among 574 employees in Singapore who commute using the Mass Rapid Transit (MRT) system. Commute preferences among telecommuters who switch to physical commutes could be attributed to these inductive effects. Among these effects, reduced crowdedness is more likely to cause the shifts away from telecommuting, more so than reduced commute times. The results also demonstrate that these effects are in turn influenced by the benefits of commuting enhanced by employment decentralisation. The significance of sociodemographic factors to these benefits is investigated as relevant practical implications surface regarding such decentralisation policies.